The unity of consciousness, within subjects and between subjects. - Roelofs, Luke (Philosophical Studies, 2016)
The unity of consciousness has so far been studied only as a relation holding among the many experiences of a single subject. I investigate whether this relation could hold between the experiences of distinct subjects, considering three major arguments against the possibility of such 'between-subjects unity'. The first argument, based on the popular idea that unity implies subsumption by a composite experience, can be deflected by allowing for limited forms of 'experience-sharing', in which the same token experience belongs to more than one subject. The second argument, based on the phenomenological claim that unified experiences have interdependent phenomenal characters, I show to rest on an equivocation. Finally, the third argument accuses between-subjects unity of being unimaginable, or more broadly a formal possibility corresponding to nothing we can make sense of. I argue that the familiar experience of perceptual co-presentation gives us an adequate phenomenological grasp on what between-subjects unity might be like.